Low-intensity focused ultrasound targeted microbubble destruction reduces tumor blood supply and sensitizes anti-PD-L1 immunotherapy - Wu, Nianhong; Cao, Yuting; Liu, Ying; Zhou, Ying; He, Hongye; Tang, Rui; Wan, Li; Wang, Can; Xiong, Xialin; Zhong, Linhong; Li, Pan (Frontiers in Bioengineering and Biotechnology, 2023)
Immune checkpoint blockade (ICB) typified by anti-PD-1/PD-L1 antibodies as a revolutionary treatment for solid malignancies has been limited to a subset of patients due to poor immunogenicity and inadequate T-cell infiltration. Unfortunately, no effective strategies combined with ICB therapy are available to overcome low therapeutic efficiency and severe side effects. Ultrasound-targeted microbubble destruction (UTMD) is an effective and safe technique holding the promise to decrease tumor blood perfusion and activate anti-tumor immune response based on the cavitation effect. Herein, we demonstrated a novel combinatorial therapeutic modality combining low-intensity focused ultrasound-targeted microbubble destruction (LIFU-TMD) with PD-L1 blockade. LIFU-TMD caused the rupture of abnormal blood vessels to deplete tumor blood perfusion and induced the tumor microenvironment (TME) transformation to sensitize anti-PD-L1 immunotherapy, which markedly inhibited 4T1 breast cancer’s growth in mice. We discovered immunogenic cell death (ICD) in a portion of cells induced by the cavitation effect from LIFU-TMD, characterized by the increased expression of calreticulin (CRT) on the tumor cell surface. Additionally, flow cytometry revealed substantially higher levels of dendritic cells (DCs) and CD8+ T cells in draining lymph nodes and tumor tissue, as induced by pro-inflammatory molecules like IL-12 and TNF-α. These suggest that LIFU-TMD as a simple, effective, and safe treatment option provides a clinically translatable strategy for enhancing ICB therapy.